FACTORS DETERMINING PERFORMANCE OF MANUFACTURING INDUSTRIES – A STUDY IN SRIKAKULAM DISTRICT, AP - Smt. Chitturi Lakshmi (Sampreshan, ISSN:2347-2979 UGC CARE Group 1, 2024)
Manufacturing sector is the backbone of Indian economy. Despite many constraints affected in the last few years, this sector occupied a place of pride covering the largest industries in India and Srikakulam district in Andhra Pradesh state also. The contribution of MSMEs in employment generation and production of goods and services found very much significant, especially in the rural and backward areas of the country. Since, they are an essential source of jobs, create entrepreneurial development and employment in rural areas, the migration of labour from rural to urban areas is controlled. Moreover, the main objective of this research paper is to find out the determining factor of manufacturing industries’ performance in Srikakulam district, the study has considered finance resources, marketing facilities, technical skills, government support, information accessibility, skilled labour, financial accessibility, financial sustainability and financial management are the independent variables and performance of manufacturing industries as the dependent variable. In this process of investigation 352 micro, small and medium scale manufacturing enterprises were taken as sample and the perceptions of entrepreneurs collected through with the help of questionnaires. To estimate this regression analysis has been done and found that marketing facilities, government support and information accessibility are indicating 1% significance, and financial awareness, skilled labour, financial sustainability and financial management are indicating 5% significance in influencing the performance of manufacturing industries in Srikakulam district, Andhra Pradesh.